Optimalisasi Material Utama Pada Auto Transformator 100 MVA - Asep Saepudin; Djoko Nursanto (LPPMPK- Universitas Muhammadiyah Cileungsi, 2020)
Autotransformator is a transformer that has primary and secondary winding with the same common winding, so that it has a lighter weight compared to ordinary power transformers. The purpose of this study is to optimize the main material used in the three-phase Auto transformer in order to get the most optimum value approaching the calculation results and to know the comparison between the calculation results and the actual use of the main material in the Auto transformer and three-phase power transformer. The main material in power transformers is copper for winding and silicon steel for cores (transformer cores). Based on this research, it can be concluded that the use of main material in Auto three-phase power transformer is less than the three-phase power transformer for the same voltage and power, the magnitude of the difference in the range of 12.5% ​​for Copper and core (transformer core) range of 47.3% of the main material in the power transformer can.